Controllable Growth of Few-Layer Niobium Disulfide by Atmospheric Pressure Chemical Vapor Deposition for Molecular Sensing - Lv, Qian; Qin, Xiaolu; Lv, Ruitao (Frontiers in Materials, 2019)
Two-dimensional metallic NbS2 has attracted increasing attentions due to its excellent properties. So far, the preparations of NbS2 are mainly focused on the mechanical exfoliation and molecular beam epitaxial (MBE), both of which have limitations, such as, small lateral sizes (usually less than 1 μm), low yield, et al.. Chemical vapor deposition (CVD) has been used to synthesize NbS2, but mainly depends on atomically flat substrates (e.g. graphene, h-BN) to grow thinner and larger sheets and the growth of NbS2 on SiO2/Si is still challenging. In this contribution, NbS2 single crystals with different layers are controllably synthesize. Few-layer NbS2 single crystals from one layer to nine layers with several tens of micrometers lateral sizes (up to ~ 20 μm) can be obtained by controlling hydrogen content in Ar/H2 carrier gas, NaCl amount, the growth temperature and the growth time, which are much larger than that synthesized by the MBE route. Meanwhile, as-synthesized NbS2 demonstrates higher sensitivity for probing trace amount of molecules than that of graphene, ascribed to the efficient charge transfer between NbS2 and molecules. To the best of our knowledge, this is the first time for NbS2 to be investigated as SERS substrates for probing molecules.